Association Between Vitamin D Exposure and Head and Neck Cancer: A Systematic Review With Meta-Analysis - Pu, Yuting; Zhu, Gangcai; Xu, Yimin; Zheng, Siyuan; Tang, Bin; Huang, Huimei; Wu, Irene X. Y.; Huang, Donghai; Liu, Yong; Zhang, Xin (Frontiers in Immunology, 2021)
Background Vitamin D deficiency is a well-described preventable cause of many cancers; the association of vitamin D use with the development of head and neck cancer (HNC) is not clear. We aim to conduct a systematic review of the studies assessing the relation between vitamin D exposure and the prevention and prognosis of the HNC using meta-analysis. Methods PubMed, EMBASE, Cochrane Library, Web of Science up to 1 January 2021, and reference lists of related studies were searched. We extracted observational studies reporting the association between vitamin D (vitamin D receptor gene polymorphisms, 25-hydroxyvitamin D concentrations, and vitamin D intake) and the outcomes of interest (HNC incidence and HNC mortality) in HNC patients aged 18 or older. Fixed effects models were used to calculate pooled effect sizes and 95% confidence intervals (CIs) by RevMan (version 5.3). Results Sixteen studies with a total of 81,908 participants were enrolled in our meta-analysis. Based on the pooled genomic analysis, comparing with participants with the genotypes of Ff + FF or FF, the pooled odds ratio (OR) of participants with the genotype of ff was 0.77 (95% CI: 0.61 to 0.97) and 0.75 (0.58 to 0.97), respectively. A similar trend was noted when comparing tt with Tt + TT or TT, in which OR (95% CI) was 0.70 (0.55 to 0.90) and 0.72 (0.55 to 0.95). No significant association was identified between BsmI polymorphism and HNC. Furthermore, the OR of HNC incidence was 0.77 (0.65 to 0.92) for participants with vitamin D intake over the ones with a regular diet. High concentrations of circulated 25-hydroxyvitamin D (25-OHD) significantly decreased by 32% of HNC incidence (OR (95% CI): 0.68 (0.59 to 0.78)) and increased HNC survival (pooled hazard ratio 1.13, 1.05 to 1.22) during a 4–5 years follow-up. High concentrations of circulating 25-OHD in patients with HNC led to a decreased risk of mortality to 0.75 (0.60 to 0.94) as the follow-up extends to 8–12 years. Conclusions Elevated activities of vitamin D by diet intake, genomic polymorphisms, or circulated 25-OHD may protect people from HNC and improve the prognosis of patients with HNC. Systematic Review Registration PROSPERO, identifier CRD42020176002 (https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=176002).